Web 2.0 : Developing the six domains in a first approach to EFL. (2021)
This work seeks to design an innovative didactic and pedagogical proposal focused on the first approach to the English language through the integration of the six domains of childhood development in activities supported by open access web 2.0 tools in a blended learning context in official institutions in the country. Also, this proposal was created to be implemented with first-grade students who are in a virtual or an educational rotation contexts due to the contingency measures implemented because of Colvid-19.